Inside relativity - Mook, Delo E., 1942- (Princeton, N.J. : Princeton University Press, 1987)
Here a physicist and a professor of literature guide general readers through the ideas that revolutionized our conception of the physical universe.
Frontmatter -- CONTENTS -- Preface -- CHAPTER 1: THE SCIENTIFIC ENTERPRISE: POSING MODELS -- CHAPTER 2: THE CLASSICAL BACKGROUND -- CHAPTER 3: THE SPECIAL THEORY OF RELATIVITY -- CHAPTER 4: SOME CONSEQUENCES OF SPECIAL RELATIVITY -- CHAPTER 5: THE GENERAL THEORY OF RELATIVITY -- CHAPTER 6: COSMOLOGICAL CONSEQUENCES OF GENERAL RELATIVITY -- CODA -- APPENDIX A: THE LORENTZ TRANSFORMATIONS AND MINKOWSKI DIAGRAMS -- APPENDIX B: EXPLANATION OF RULES I AND II FOR SOLVING THE LORENTZ TRANSFORMATIONS IN MINKOWSKI DIAGRAMS -- APPENDIX C: THE TROUBLE WITH TACHYONS -- APPENDIX D: MAXWELL'S EQUATIONS, ELECTROMAGNETIC WAVES, AND SPECIAL RELATIVITY -- Glossary of Technical Terms -- Suggestions for Further Reading -- Index.
JSTOR
Keywords: Relativity (Physics); Relativité (Physique); SCIENCE -- Energy; SCIENCE -- Mechanics -- General; SCIENCE -- Physics -- General; Relativity (Physics)